Teacher Education During COVID-19 Pandemic: A Review of Literature During School Closures - Masooma Ali Al-Mutawah (Journal of Educational Issues, 2024)
The closure of schools as a response to the COVID-19 pandemic led to an urgent shift towards remote and online learning. This sudden shift necessitated significant adjustments in teacher education. Educators had to swiftly adapt their instructional methods to cater to the requirements of distance education. Understanding the experiences and strategies employed by teacher education institutions, educators, and pre-service teachers during this period is crucial for shaping future practices and policies. This study seeks to analyze a variety of research articles conducted both during and post the COVID-19 pandemic. The objective is to explore the main dimensions covered in these studies, focusing on the concerns or challenges faced by their teaching training programs. By examining the insights gleaned from these studies, we aim to gain a comprehensive understanding of the adjustments and innovations that emerged in response to the pandemic. This analysis will provide valuable insights into how teacher education programs can effectively navigate similar challenges in the future and continue to evolve in the face of changing educational landscapes.